Conservacionismo y nuevos usos del suelo en el Bajo Amazonas y en la Norpatagonia chilena: una discusión sobre renta territorial y vocación espacial en el contexto del capitalismo contemporáneo - Luis Fernando De Matheus; Andrei Cornetta (Confins, 2020)
This paper aims to discuss theoretically some of the geographical breakdowns related to the processes of conversion of nature and landscape into commodities, whose value is constituted from a contradictory relationship between scarcity and rarity. We understand this relationship as part of a process that potentialized and diversifies the different ways of extracting territorial rents, promoting considerable changes in its spatial vocation. As a potential capital, the “preserved space” is a reserve of value that expands directly in relation to its possibilities of use. Thus, these processes are discussed as a movement of spatial resignification, emphasizing how the practices and discourses built around environmental conservation are driven or modifying the conformation of new territorial rents. From a critical perspective, and of our own reflections, arising from our respective investigations in the Brazilian Amazon and in Chilean Norpatagonia, we try to advance some theoretical questions about the process that has renewed and complicated the ways of extracting territorial income in both regions, loaded with diversity and particular symbology’s. Although these regions have enormous historical and geographical differences between them, both constitute quite representative cases of how capital, through discourse and “conservationist” practices, has managed to reproduce itself in rural space of South America today.